Peran Ustadzah dalam Membentuk Etika Belajar Santri Perempuan melalui Pembelajaran Al-Qur’an - Chabib, Mudzakir; Subando, Joko (TSAQOFAH, 2025)
This study is motivated by the limited research on the role of ustadzah as an ethical role model (uswah hasanah) who consciously applies humanizing education, despite its significant impact on shaping female students’ learning ethics. The research aims to explore in depth the role of ustadzah as uswah hasanah in shaping students’ learning ethics through Qur’anic learning. A descriptive qualitative case study approach was employed, involving ustadzah, female students (santriwati), and pesantren leaders selected through purposive sampling. Data were collected through in-depth interviews, participatory observation, and document study, then analyzed using the Miles and Huberman interactive model. The findings show that the role of ustadzah is significant and multidimensional, encompassing functions as a teacher, mentor, and ethical role model. The study affirms that the exemplary conduct of ustadzah is a crucial element in shaping students’ learning ethics. The conclusion emphasizes the importance of the ustadzah’s holistic role in creating a learning environment that supports comprehensive character and ethical development. The implications include enriching the literature on the multidimensional role of ustadzah and providing practical recommendations for pesantren and ustadzah to enhance training in humanizing education, while also opening opportunities for further studies on modern challenges to the personal inculcation of Qur’anic values.